NAFTA on the Brink - Geoffrey Gertz (Intereconomics, 2018)
The new regulatory framework in the digital sector in Europe is likely to fall short of expectations. A fragmented digital market with insuffi cient incentives for investment is the probable outcome. European regulators should abandon their approach in favour of a new and more flexible set of ideas discussed in this paper.
Keywords: 330; Canada; Free trade agreements; Mexico; Protectionism; USA; NAFTA